Patient-reported outcome measures in presbyopia: a literature review. Issue 1 (12th July 2020) - Sharma, Garima; Chiva-Razavi, Sima; Viriato, Daniel; Naujoks, Christel; Patalano, Francesco; Bentley, Sarah; Findley, Amy; Johnson, Chloe; Arbuckle, Rob; Wolffsohn, James
Abstract : Presbyopia is the age-related loss of near-distance focusing ability. The aim of this study was to identify patient-reported outcome measures (PROMs) used in clinical trials and quality-of-life studies conducted in individuals with presbyopia and to assess their suitability for use in individuals with phakic presbyopia. Literature searches were performed in Medline and Embase up until October 2017. Specific search terms were used to identify presbyopia studies that included a PROM. All clinical trials with PROM-supported endpoints in presbyopia were identified on ClinicalTrials.gov. Further searches were conducted to retrieve articles documenting the development and psychometric evaluation of the PROMs identified. A total of 703 records were identified; 120 were selected for full-text review. Twenty-one clinical trials employed PROMs to support a primary or secondary endpoint. In total, 13 PROMs were identified; a further 23 publications pertaining to the development and validation of these measures were retrieved. Most PROMs were developed prior to release of the Food and Drug Administration (FDA) 2009 patient-reported outcome guidance and did not satisfy regulatory standards. The Near Activity Visual Questionnaire (NAVQ) was identified as the most appropriate for assessing near-vision functioning in presbyopia. While the NAVQ was developed in line with the FDA guidance, the items do not reflect changes in technology that have occurred since the questionnaire was developed in 2008 (eg, the increase in smartphone use), and the measure was not validated in a purely phakic presbyopia sample. Further research is ongoing to refine the NAVQ to support trial endpoints related to changes in near-vision functioning associated with phakic presbyopia.